Jasmin Hristov , Paramilitarism and Neoliberalism: Violent Systems of Capital Accumulation in Colombia and Beyond (2016)
Massive violence exerted by paramilitary groups has been a gruesome central feature of Colombia’s protracted armed conflict. Particularly in the past thirty years, paramilitary atrocities have critically affected small farmers, human rights defenders, community and labour leaders, and leftist intellectuals and politicians. But who and what are the paramilitaries and how did they emerge as key players in the armed conflict? Which sectors of Colombian society are supporting them? Why has the state not confronted them or, worse, has acted in collusion with them? Was the demobilization of the paramilitary United Self-Defense Forces of Colombia (AUC) some ten years ago a farce, leading to the transformation of the paramilitary groups but not to their extinction? These and other related questions have exercised and tormented many minds in the past decades, both in Colombia and abroad. But finding cogent and persuasive answers remains work in progress.